Marías. Entre la adoración y el estigma - Montesinos Castañeda, María (Filanderas, 2023)
Marías. Entre la adoración y el estigma originated in the seminar “Between adoration and stigma: mothers, virgins, and prostitutes.” This event was an extra activity of the course “Analysis and interpretation of the image,” taught in the Art History and History Bachelors at the Universitat de València. In addition, the writers of this book are members of the research roup “Apes. Estudis de Cultura Visual de la Universitat de València,” which included this seminar as a part of their Educational Innovation Project (2019-2020).